Infancy Oral Hygiene - Abudaqqa, Zaid J. A.; Nanobashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2020)
Overview:Infants aren’t as associated with oral hygiene as they should be. Infancy (period of early childhood) is a critical time to establish habits, both good and bad, that have the potential to affect an individual’s future oral health as well as overall health and well-being into adolescence. It should be taken much care about infancy for it to be considered the first building block of a human’s life, as any tiny obstacle might ruin the future of the infant. All circumstances of prevention must be applied seriously regarding the infant’s oral health including all its proportions, for the oral health to be considered an important aspect of life quality which affects eating, comfort, speech, appearance, and social acceptance. From the other side, some infants might have oral disturbances which if not treated on time can cause permanent obstruction. Good child observation and knowledge will help passing through such obstacles thoroughly. There is a lot of sequences for prevention considered toward infant’s oral health. Conclusion: Infant oral health (IOH) is a preventive service advocated by major medical and dental organizations. IOH is the child’s first visit to dental office (between 6 and 12 months of age) for dental caries risk assessment and other types of examinations. IOH is advocated by American Academy of Pediatric Dentistry (AAPD), the American Dental Association, and the American Academy of Pediatrics, among major health organizations.